A Model of the Joint Distribution of Banking and Exchange-Rate Crises - Marion, Nancy; Flood, Robert (Washington, D.C. : International Monetary Fund, 2001)
We develop a simple framework for studying the joint distribution of banking and currency crises triggered by real shocks. Our framework illustrates the fact that bank and currency collapses are related but they are not the same thing. Studying currency and bank collapses either in isolation or in perfect correlation with each other is inappropriate, producing biased estimates of the likelihood of crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet